Revising the Chronologies of the Hellenistic Colonies of Samarkand-Marakanda (Afra- siab II–III) and Aï Khanoum (northeastern Afghanistan) - Lerner, Jeffrey D. (Anabasis. Studia Classica et Orientalia, 2010)
The current dating system of Hellenistic Samarkand (Marakanda, Afrasiab II) and Aï Khanoum, two Greek cities in the Hellenistic Far East, stems from the 1998 work of B. Lyonnet. The present article questions the basis of her proposed chronology and introduces new evidence for revising it. The article relies primarily on archaeology, ceramics, numismatics, and epigraphy. The result is a different interpretation of how long both sites were under Greek hegemony. In the case of Samarkand, there is not sufficient evidence to warrant Lyonnet’s notion that the Greeks abandoned the city on two different occasions with an interval of about a century separating each event. The archaeological record does not allow for the clear distinction between Hellenistic Samarkand (Afrasiab II) and Samarkand under nomadic control (Afrasiab III). As such, we are compelled to retain the chronology of the site as it was initially conceived in 1950 by Terenozhkin for Afrasiab II-III. In order to place this material in a wider historical context, I have followed Lyonnet’s convention of drawing upon relevant comparisons from Aï Khanoum. The Greeks of both cities may well have enjoyed a political autonomy far longer than is currently believed.